The Influence of Sustainability Report Disclosure on Financial Performance - Yuniar, Madewi Arum Kusuma; Wijayanti, Rita (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
In Indonesia, sustainability reports are increasingly recognized as a form of corporate commitment to the sustainability of the global economy. Several previous studies have shown that disclosure of sustainability reports can affect a company's financial performance, although the results still vary. In addition to sustainability reports, other factors can affect a company's financial performance, such as company size and leverage. This study uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, which is analyzed with the help of SmartPLS 4 software. This study uses a quantitative method with a causal-comparative approach to analyze the relationship between sustainability reports and company financial performance. The analysis used is multiple linear regression. The population used in this study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The results of this study indicate that sustainability reports and company size affect financial performance (ROA), while leverage does not affect financial performance (ROA), and sustainability reports, leverage, and company size do not affect company value (Tobin's Q).